PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HAND & BODY LOTION VASELINE - Lala Pebriyanti (2022)
This research aims to determine the influence and how much influence the variables of purchase decisions are affected by the variable brand image, price and quality of the product on hand and body lotion Vaseline The study is a quantitative study using primary data sources with descriptive analysis techniques using SPSS and inferential analysis techniques using SmartPLS (Partial Least Square) as the tools used in the research. The target of the population of this study is all the z generation users hand and body lotion Vaseline in Jakarta with a sample used by 102 respondents. Using sampling techniques and observational sampling methods. The result of this study suggests that variable brand image, price and product quality have significant impact on the decision to purchase hand and body lotion Vaseline. Based on the results of the more powerful variable statistics on the decision of purchase, there is a variable brand image that shows 0.269 and then the price of 0.244 and the quality of the product at 0.235.